Community-Led Carbon Credit Projects: A Comparative Analysis Of Success Factors In Timor-Leste - Guterres Lopes da Cruz, Cesaltino (Jurnal Syntax Fusion, 2024)
This research conducts a comparative analysis of the factors contributing to the success of community-led carbon credit projects in Timor-Leste. Its aim is to provide insights into effective strategies for combatting climate change and empowering local communities. Utilizing a mixed-methods approach, both qualitative and quantitative techniques were employed to assess critical success factors, such as community engagement, project governance, financing mechanisms, and environmental impact assessment. Diverse data collection methods were applied, including literature review, interviews with key stakeholders, surveys of local communities, document analysis, and field visits to project sites. The study emphasizes the importance of active community involvement, well-defined governance frameworks, accessible funding, and thorough environmental impact assessments for achieving successful project outcomes. Additionally, recommendations are offered to address challenges and enhance the scalability and sustainability of community-led carbon credit projects in Timor-Leste. This research contributes to the advancement of knowledge regarding best practices and lessons learned in community-led climate initiatives, with implications for policy, practice, and future research directions.